Beauty or statistics : practice and science in Dutch livestock breeding, 1900-2000 - Theunissen, Bert, 1955- (University of Toronto Press, 2020)
"This book is a valuable and innovative piece of scholarship. It advances the broadening field of studies devoted to understanding how animal breeding has evolved after the advent of the science of genetics. Animal breeding is an ancient human occupation, but it has undergone profound changes which have stressed and modified old ways over the past 120 years. This book looks at the interface between science and practice in the breeding of farm animals with a special focus on Dutch livestock breeding. It argues that it is too simplistic to see the infiltration of genetics into practice as merely modernization."--